(untitled) (Lehahayer, 2015)
The genealogy of the Torosowicz family: the ancestors and relatives of archbishop Mikołaj Torosowicz, the creator of the union between Polish Armenians and the Catholic Church Since 1627 Mikołaj Torosowicz (1605-1681) was the bishop of Polish Armenians and resided in Lvov; he was subordinated to the catholicos of all Armenians in Etchmiadzin. In 1630 he issued the act of the union of his diocese with the Catholic Church, which initiated a new church structure which exists to this day – the Armenian Catholic archiepiscopate of Lvov, directly dependent upon the papacy. The article features a reconstruction of the bishop’s family milieu, his genealogical relations with the more prominent families of Lvov Armenians, the economic activity, the social position in the Armenian community, the city of Lvov and the Polish society, the promotion to the noble estate of some lines of the Torosowicz family. Special emphasis was placed on the attitude to the religious practices and the accretion of relationships regards Catholicism in the generations of the archbishop’s ancestors. The analysis also involves the attitudes of his relatives toward the decision about establishing a church union with Rome.